Evaluation of the API 20 c microtube system for the identification of clinically important yeasts. - Roberts, G D (1976)
The API 20 C microtube system containing 20 biochemical tests for the identification of yeasts was compared with conventional tests used in the Mayo Clinic mycology laboratory. Three hundred isolates of clinically important yeasts were studied, and agreement of the carbohydrate fermentation and assimilation tests between the systems was good. The API 20 C represents a useful, commercially available screening method for the identification of yeasts; however, it is not a complete system and must be used in conjunction with microscopic morphological features and, when appropriate, with other biochemical tests.